Using a survey, analyzing the current situation of allergic March in elementary and junior high school students of oyama and tochigi cities, Japan - Hamid Abid; Yusuke Ando; Manabu Miyamoto; Shigemi Yoshihara (Elsevier, 2024)
Background: Over the past few decades, allergic diseases have become more prevalent and impact around 20% of the global population. There is clinical significance of allergic march as it places a burden on the quality of life of children and their families. Objectives: To assess the current situation of allergy conditions experienced by children attending elementary and junior high schools in Oyama and Tochigi cities, Japan. Methods: A letter was sent to parents informing them about an opt-in online survey concerning children's allergies along with a weblink and a QR code. A video explained the survey process and informed parents that their replies could not be retracted. Parents who had watched the explanation video and answered yes to participating were considered to have provided consent for the survey. Results: A total of 2038 valid replies were gathered. Allergic Rhinitis was the most commonly diagnosed allergy, followed by Asthma, Food Allergy, and Atopic Dermatitis. Around 70% of the children were affected by the allergies, of whom half had been affected by multiple allergies. Most children affected by Atopic Dermatitis, Food Allergy or Asthma were affected by other allergies. Atopic Dermatitis and Food Allergy were mostly diagnosed before Asthma and Allergic Rhinitis. Conclusions: Children who are diagnosed with either Atopic Dermatitis or a Food Allergy will likely be affected by other allergies later in life. Allergic march perpetuated an earlier peak diagnosis incident rate for allergic rhinitis. Allergic Rhinitis can occur independently from other allergies compared to Atopic Dermatitis, Food Allergy and Asthma.